Regulation and pathophysiological role of epithelial turnover in the gut. - Günther, Claudia; Buchen, Barbara; Neurath, Markus; Becker, Christoph (Seminars in Cell & Developmental Biology, 2014)
Cell death in the intestinal epithelium has to be tightly controlled. Excessive or misplaced epithelial cell death can result in barrier dysfunction and, as a consequence thereof, uncontrolled translocation of components of the microbial flora from the lumen into the bowel wall. Susceptibility to gastrointestinal infections or chronic inflammation of the gut, as observed in patients with inflammatory bowel disease, can be the result of such dysregulation. Conversely, defects in cell death initiation might lead to an irregular accumulation of epithelial cells and cause intestinal cancer development. Until recently, activation of caspases in the intestinal epithelium was considered as a potential contributor to barrier dysfunction and as a pathogenic factor in the development of intestinal inflammation. Thus blocking of caspases appeared to be a potential therapeutic option for patients with inflammatory bowel disease. Recent studies on necroptosis however demonstrated that also inhibition of caspases can cause barrier dysfunction and intestinal inflammation. Caspase-8 on top of its functions in the extrinsic apoptosis pathway also controls necroptosis and turns out to be an essential molecule in regulating tissue homeostasis in the gut. Epithelial caspase-8 therefore emerges as a checkpoint not only of cell survival and cell death, but also as a regulator of the mode of cell death. According to this model, both excessive activity as well as a lack of activity of caspase-8 results in epithelial cell death and intestinal inflammation and caspase-8 needs to be tightly controlled to warrant tissue homeostasis in the gut.
Keywords: Inflammation; Necroptosis; Ripoptosome